Economic growth in the Caribbean (ECLAC [Santiago]CL, 2009)
Discusses growth performance during the last five decades from different perspectives. Explores the exent to which the convergence hypothesis implied by the Solow model is valid to the Caribbean. Undertakes a growth in accounting exercise, with and without the inclusion of human capital. Explores the determinants of economic growth.
Bibliography: p. 28-29